Realizing the value of grassland ecosystem services: global practice and its inspiration for the karst desertification control area - Li, Yongyao; Xiong, Kangning; Song, Shuzhen; Zhang, Wenfang (Frontiers in Sustainable Food Systems, 2024)
The conflict between grassland ecosystem conservation and economic development is an important but challenging question. Realizing the value of ecosystem services (ES) is considered to be a solution for the dual sustainability of ecology and economy. However, there is a lack of systematic understanding of value realization of grassland ES, especially in the karst desertification (KDC) area, which is still at an exploratory stage. We obtained 527 studies from 48 countries in the past 20 years through the Scopus database, and systematically reviewed the current understandings and practices by the content analysis method, and enlightened the inspiration for the grassland in the KDC area. Results showed that: (i) Over the past 20 years, the literature number showed a fluctuating growth trend, and the study areas are mainly concentrated in economically developed countries with rich grassland resources; (ii) Pathways such as grassland management and payment for ecosystem services (PES) are widely used to improve grassland ES and human well-being, and most studies have shown positive effects; (iii) Their performance is significantly impacted by stakeholders, governments, as well as the attributes of ES, and a path of government-led, stakeholder participation and market-oriented operation should be explored; and (iv) There are still some knowledge gaps, such as, uneven distribution of study areas, few effective pathways for realizing the public grassland ES value, and deficient linkage mechanisms of “grassland ES-industry development-economic system feedback-ecosystem protection,” and so on. Based on our findings, we not only make recommendations for the current dilemma of realizing the value of grassland ES, but also put forward the enlightenments to the grassland in the KDC area based on experiences and lessons learned from global practices. The results can provide theoretical guidance for the ecological protection and sustainable development of grasslands in fragile areas.